Authority of Sarak Opat in Settlement of Environmental Pollution Cases - Surya, Achmad; Suhartini, Suhartini; Hakim, Ruslan (Widya Yuridika, 2024)
The existence of fishing gear type padang hoe began to spread in the area of Lake Lut Tawar, Central Aceh. As a result of massive and uncontrolled fishing practices and disregard for local culture, this is very dangerous for the preservation of Lake Lut Tawar. So if it continues to be left unchecked, fish endemic to Lake Lut Tawar, such as the depik fish, are threatened with extinction. In the Gayo community in Central Aceh District, cases/disputes that occur within the community are resolved by a customary institution called sarak opat. The purpose of this study is to find out the authority of sarak opat in solving environmental pollution and to find out the obstacles of sarak opat in solving environmental pollution. This type of research is empirical normative research. The data sources used are primary data and secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. The method of collecting data is through interviews and document studies. The way of analyzing the data that has been collected from both primary and secondary data will be analyzed qualitatively, so that it is found that facts as symptoms of primary data are associated with theories from secondary data presented descriptively. The results of the study explained that sarak opat's authority has a legal basis for resolving environmental pollution cases, as mandated in the Aceh Qanun and the Aceh Governor's Regulations concerning Implementation. Customary and Indigenous Dispute/Dispute Resolution. custom. Obstacles to the sarak opat customary institution in resolving environmental pollution cases, namely: First, the loss of the function of the Pawang Lut in Gayo society. Second, there is a lack of understanding of the apparatus of the Sarak Opat customary institution regarding the authority to settle cases of minor environmental pollution.